Glycoproteoforms of Osteoarthritis-associated Lubricin in Plasma and Synovial Fluid - Afshari, Ali Reza; Chang, Vincent; Thomsson, Kristina A.; Höglund, Jennifer; Browne, Elizabeth N.; Karadzhov, George; Mahoney, Keira E.; Lucas, Taryn M.; Rangel-Angarita, Valentina; Ryberg, Henrik; Gidwani, Kamlesh; Pettersson, Kim; et al. (Elsevier BV, 2025)
Lubricin/proteoglycan-4 (PRG-4) is a mucinous glycoprotein that lubricates cartilage and maintains normal tissue function and cell homeostasis. Altered O-glycoproteforms of lubricin have been found in osteoarthritis (OA) synovial fluid (SF), which could ostensibly be used to diagnose early onset OA. However, SF is invasive to obtain and generally would not be surveyed from otherwise healthy individuals. Thus, a plasma-based OA screening tool focused on lubricin glycosylation could be a less invasive method to aid in early-stage OA diagnosis. In this report, we used glycomics and glycoproteomics to characterize glycoproteoforms of OA lubricin in SF and plasma. We obtained near-complete sequence coverage of lubricin's mucin domain and its glycosylation using matched SF and plasma from patients with OA (N = 5). From SF lubricin we observed a spectrum of O-glycans ranging from a single GalNAc alpha 1-Ser/Thr monosaccharide up to branched pentasaccharides. In contrast, plasma based lubricin was predominantly decorated with sialylated Gal beta 1- 3GalNAc alpha 1-Ser/Thr (Sialyl T). To explain the glycosylation differences observed between SF and plasma lubricin, we present splice variant-specific peptides found within the non-glycosylated region, revealing that that the longest spliceoform of lubricin was present exclusively in SF, while additional shorter splice variants could only be detected in plasma. Based on our glycoproteomic data, we developed and validated a lectin assay for lubricin, and applied this on a larger cohort of matched SF/plasma (N = 19) to confirm the glycosylation differences between SF and plasma proteoforms. Next, we leveraged our assay to screen over 100 patient with OA samples (OA patients N = 108/controls N = 38) to probe plasma lubricin as an OA biomarker. Here, we detected a decrease in alpha 2,6 linked sialic acid in patients with OA and further show that the extent of alpha 2,6 and alpha 2,3 sialylation on plasma-associated lubricin correlated with patient characteristics, especially Body Mass Index (BMI).